2019
DOI: 10.11648/j.ijaas.20190503.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Rhizobium</i> Inoculation and Phosphorus Fertilizer Rates on Growth, Yield and Yield Components of Chickpea (<i>Cicer arietinum L.</i>) at Goro, Bale Zone, Oromia Regional State

Abstract: Chickpea (Cicer arietinum L.) is an important legume crop in Ethiopia. However, the productivity of the crop is very low due to a number of constraints out of which soil nutrient depletions a serious problem. Field experiment was conducted in 2015/16 in Goro, Bale Zone, Oromia Regional State to determine the effectiveness of Rhizobium strains and phosphorus fertilizer application on two varieties of chickpea (Arerti and Habru). The thirty treatments included: two Rhizobial inoculants (EAL018andEAL029), five P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…It is required for efficient and early root development [23], N 2 -fixation (enhanced nodulation) [24,25], increased leaf size and branching [26], photosynthesis process [27], constituents of ATP and ADP [28], flowering, seed formation [28], grain yield [29], increased resistance to plant diseases [30], and hastening crop maturity [22]. However, P has most frequently been identified as a deficient nutrient in most soils especially in the tropics [31,32], and it makes the situation most serious since the P necessity of legumes is greater as compared to cereals [33]. Hence, the use of an optimum rate of P fertilizer and improved P use efficiency have a major effect on enhancing the growth and productivity of legume crops such as chickpea [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is required for efficient and early root development [23], N 2 -fixation (enhanced nodulation) [24,25], increased leaf size and branching [26], photosynthesis process [27], constituents of ATP and ADP [28], flowering, seed formation [28], grain yield [29], increased resistance to plant diseases [30], and hastening crop maturity [22]. However, P has most frequently been identified as a deficient nutrient in most soils especially in the tropics [31,32], and it makes the situation most serious since the P necessity of legumes is greater as compared to cereals [33]. Hence, the use of an optimum rate of P fertilizer and improved P use efficiency have a major effect on enhancing the growth and productivity of legume crops such as chickpea [34].…”
Section: Introductionmentioning
confidence: 99%
“…International Journal of Agronomy process of N 2 -fixation is largely sensitive to the deficiency of P, via its influence on the growth and survival of rhizobia, nodule formation, nodule functioning, and growth of the host plants [22,75]. Although there are various studies in relation to the effects of separate/integrated use of P rate and rhizobium inoculation on nodulation, growth, and yield of chickpea [32,76], there has not been a review about such research findings; hence, considering its significance, the aim of this paper is to review the effect of P rates and rhizobium inoculation on nodulation, growth, and yield of chickpea.…”
Section: Introductionmentioning
confidence: 99%
“…Similar result was also reported by Dutta et al (1998) in lentil who observed that the bacterial isolate treated genotypes which had capacity to early higher TDM and growth rate also showed higher seed yield. Further, the bio-fertilizer effect on growth and biomass production of legume crops has been studied (Iqbal et al, 2012;Hossain et al, 2014;Meleta and Abera, 2019) Haque et al, 2014 and found that bio-fertilizer treatment improve plant growth and development. In this study, bio-fertilizer treated plants produced higher TDM than non-biofertilizer treated plant that supported the earlier findings.…”
Section: Methodsmentioning
confidence: 99%
“…Readily available nitrogen helps to increase more photosynthesis and dry matter accumulation as well as increase leaf area index, thereby enhance biomass of root and shoot resulting bearing more pods and seeds pod -1 , 1000-grain weight of legume crops and performed more seed yield. Meleta and Abera (2019) stated that Rhizobium inoculants increased the grain yield of chickpea by 10.4-19.3% over uninoculated control. Tiwari et al (2018) reported that inoculation of Rhizobium influenced maximum seed yield of lentil comparing with control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation